Trouble in Paradise: Expanding Applications of the Getty Thesaurus of Geographic Names® to Enhance Intellectual Discoverability of Circum-Caribbean Materials - Gooding, Alexandra (KULA)

(untitled) (University of Victoria Libraries, 2022)
This article examines how the Circum-Caribbean region’s cultural and geographic complexities make it difficult to describe or index relevant archival materials using the mainstream authority controls used in galleries, libraries, archives, and museums (GLAMs). This difficulty stems from the fact that authority controls utilised by GLAMs are primarily created by North American or European authorities and, therefore, have Western-centric views imbued with colonialist overtones. When these systems are used to catalogue, index, or describe Circum-Caribbean-related collection materials, a tension arises: a system with a white, Euro-American perspective is applied to material reflective of a significantly multicultural place, culture, subject, and population. The rigidity of controlled vocabularies and their applications—which typically follow specific indexing methodologies—cannot accommodate the fluidity necessary to accurately denote the complex Circum-Caribbean region, especially with regard to geographic indexing. This article demonstrates the difficulties that emerge from trying to delimit and define the Caribbean region; provides an abbreviated analysis of the Circum-Caribbean’s representation in the Getty Thesaurus of Geographic Names® (TGN), which mirrors the difficulties of defining and delimiting the region; and presents a case study in which the West Indian Postcard Collection at Cambridge University Library was indexed using augmented applications of the TGN. The research presented in this paper supports the theory that employing both general and specific indexing strategies creates enhanced access to Caribbean-related collection materials by enabling regional, sub-regional, and territorial/national avenues to retrieve collection materials.